Energy Efficiency Improvement Through Pinch Analysis of Gas Phase Chlorination Process of Propylene - Hasna Haniya; Tita Ayu Windarti; Diva Nanda Paramitha (Journal of Vocational Studies on Applied Research, 2025)
Dependence on imports of raw materials such as allyl chloride amid the rapid development of the national chemical industry is the background for optimizing energy efficiency in the preliminary design of this 15,000 ton/year capacity plant. Given that the production process involves an exothermic gas phase chlorination reaction at extreme temperatures (510 K), the use of Pinch Technology is crucial to minimizing energy consumption. This study utilizes HINT software to identify heat and cold flows, set the most favorable ΔTmin temperature threshold, and formulate a Composite Curve to map the potential for heat integration in the system. The research shows that through the identification of pinch points; the Maximum Energy Recovery (MER) target can be achieved by integrating waste heat from the reactor outlet stream to independently heat the feed before it enters the furnace unit. The implementation of this optimized heat exchanger network has been proven to significantly reduce the use of external utilities, such as Dowtherm A and cooling water, which ultimately lowers the plant's total annual costs. Overall, the application of pinch technology-based heat management strategies is a fundamental step in strengthening the economic value and operational sustainability of allyl chloride production.